2023
DOI: 10.1007/s00216-023-04678-8
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for optical chemical multi-analyte imaging

Abstract: Simultaneous sensing of metabolic analytes such as pH and O2 is critical in complex and heterogeneous biological environments where analytes often are interrelated. However, measuring all target analytes at the same time and position is often challenging. A major challenge preventing further progress occurs when sensor signals cannot be directly correlated to analyte concentrations due to additional effects, overshadowing and complicating the actual correlations. In fields related to optical sensing, machine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Despite good spectral separation between the emission of sensor and references dyes and sample fluorescence, we still found that minor overlaps between the sensor emission and Chl fluorescence and/or sample scattering could affect the calibration and sensor performance, therefore calling for sample-specific calibration procedures. Zieger and Koren 21 demonstrated how machine-learning algorithms can be employed to optimize the precision of combined imaging of O 2 and pH in simple calibration experiments. While such an approach was beyond the scope of the present paper, machine learning could potentially also be used to help optimize sensor calibration in more complex settings, where sample fluorescence and scattering affect the ratiometric read-out.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite good spectral separation between the emission of sensor and references dyes and sample fluorescence, we still found that minor overlaps between the sensor emission and Chl fluorescence and/or sample scattering could affect the calibration and sensor performance, therefore calling for sample-specific calibration procedures. Zieger and Koren 21 demonstrated how machine-learning algorithms can be employed to optimize the precision of combined imaging of O 2 and pH in simple calibration experiments. While such an approach was beyond the scope of the present paper, machine learning could potentially also be used to help optimize sensor calibration in more complex settings, where sample fluorescence and scattering affect the ratiometric read-out.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Subsequent deconvolution of the hyperspectral data enabled O 2 imaging at a high dynamic range with the combined sensor material. Zieger and Koren 21 also demonstrated the use of machine-learning algorithms for optimizing simultaneous hyperspectral imaging of pH and O 2 based on the analysis of detailed calibration experiments.…”
mentioning
confidence: 99%
“…In this context, we have already shown that depending on the strength of the optical overlap of the different receptors, signal deconvolution can be achieved either with simpler algorithms such as spectral linear combination and least-square fitting 72 or with more complex machine learning algorithms. 74…”
Section: The Road To Multiparameter Sensorsmentioning
confidence: 99%
“…Machine learning approaches offer thereby a great opportunity to process these data sets and translate them into valuable, multiparametric information. 74,105–107 Moreover, in recent years, more and more deep learning algorithms have been reported not only for image classification but also for multiparameter regression purposes. 108 For more details on recent advances in chemometric calibration methods in modern spectroscopy, the interested reader is referred to the respective review by Wang et al 79…”
Section: The Road To Multiparameter Sensorsmentioning
confidence: 99%